SCIENCE@ALORSETAR TO OFFER BLENDED LEARNING TO STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 24 September 2016 – TheScience@AlorSetar (mailto:Science@AlorSetar) programme, a new campus of Universiti Sains Malaysia (USM), is making innovations in education with the offering of blended learning in the teaching and learning activities for new students of the campus.